Challenges of implementing management accounting innovations: Evidence from the field. (7th March 2023) - Oyewo, Babajide; Tanvir Hussain, Syed; Simbi, Chipo
Abstract : This study investigates the challenges of implementing innovative management accounting techniques, referred to as strategic management accounting (SMA), the interrelationship among the challenges and the impact of the challenges on SMA usage intensity. From the analysis of survey data obtained from listed manufacturing companies in Nigeria, the result supports the conclusion that SMA implementation challenges are interrelated. However, lack of top management support and low awareness/lack of knowledge are contributory to most of the implementation challenges. The challenges discouraging the intensive use of SMA are the perception that SMA implementation is unnecessary as strategy issues are already integrated in other functions within the organization, high implementation cost and problems relating to information flow between departments within the organization. The current study contributes to knowledge in the sense that it is the first (to the researchers' knowledge) to examine specifically the interrelationship among SMA implementation challenges in the Nigerian context, thereby drawing attention to the need to consider the challenges to embracing management accounting innovations holistically. Knowledge of SMA implementation challenges could help explain the low adoption rate of SMA in developing countries. Such knowledge might be helpful in providing a robust response to the challenges of implementing management accounting innovations.